ANALISIS PENGARUH PAD, DAU, DAK DAN BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI KALIMANTAN BARAT - B21110031, Yayat Supriatna (Jurnal Pembangunan dan Pemerataan, 2015)
ABSTRACTLocal governments need to increase capital investment in fixed assets, such as: equipments,buildings, infrastructures, and other fixed assets. Capital expenditure allocation was based on thelocal needs for facilities and infrastructure. The higher level of capital investment expected to improvethe quality of public services, because the fixed assets due to capital expenditure is a key for theimplementation of governmental duties and provides services to the public.This study was aimed at analyzing the corelations of local own revenues, general allocationfunds, and specific allocation funds with capital expenditures at Tolitoli Regency in Central SulawesiProvince. Research design methods is the field research by correlation analysis.Test results showed a lack relationship between local own revenues with capital expendituresby R value was 0,155. Meanwhile the relationship between general allocation funds with capitalexpenditures was 0,981 and special allocation funds with capital expenditures was 0,427. It shows theclose relationship between the two variables with capital expenditures.